Role of an immunisation advisory clinic. Issue 6525 (5th April 1986) - Lingam, S; Miller, C L; Pateman, J
Abstract : An immunisation advisory clinic was set up in Redbridge in 1984 to try to allay the anxieties of parents and doctors about vaccination against whooping cough and measles. The parents agreed to vaccination for 54 out of 67 children against whooping cough and 54 out of 57 against measles. Most of the 117 children who were referred to the clinic probably would not have been vaccinated, although only two had valid contraindications.